Computer-Aided Design and Manufacturing Cutting and Drilling Guides with Prebent Titanium Plates Improve Surgical Accuracy of Skeletal Class III Malocclusion. Issue 5 (May 2020) - Li, Kehan; Li, Jiayang; Du, Wen; Xu, Chunwei; Ye, Bin; Luo, En
Abstract : Background: The aim of this study was to evaluate the effects of the use of computer-aided design and manufacturing cutting and drilling guides with prebent titanium plates for the correction of skeletal class III malocclusion. Methods: In this prospective, randomized, controlled clinical trial, 46 patients with skeletal class III malocclusion were randomly assigned into two groups. The patients underwent bimaxillary surgery with computer-aided design and manufacturing cutting and drilling guides with prebent titanium plates (experimental group) or computer-aided design and manufacturing splints (control group). Preoperative and postoperative imaging data were collected and then analyzed using Mimics Research 19.0, Geomagic Studio, and IBM SPSS Version 21.0. Results: Deformity evaluation and posttreatment assessment were performed for all patients. The experimental group had fewer postoperative complications. Comparison of the linear and angular differences to facial reference planes revealed more accurate repositioning of the mandible and condyles in the experimental group, although the position of several landmarks still requires small adjustments. Conclusion: Computer-aided design and manufacturing cutting and drilling guides with prebent titanium plates effectively corrected skeletal class III malocclusion, providing positional control of segments with reasonable surgical accuracy. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, II.